2017
DOI: 10.1785/0220160186
|View full text |Cite
|
Sign up to set email alerts
|

Model Update May 2016: Upper‐Mantle Heterogeneity beneath North America from Travel‐Time Tomography with Global and USArray Data

Abstract: P-wave travel-time residuals from USArray helped improve the scale and consistency with which the mantle beneath North America is resolved. Beginning in 2008, we published a series of P-wave velocity models based on a global ray theoretical inversion of USArray and global catalog data. Here, we present the final model update, MITP_2016MAY, which includes the complete set of travel-time residuals from USArray Transportable Array (TA) in the contiguous United States. In this model, the area of high resolution ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
89
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(104 citation statements)
references
References 16 publications
15
89
0
Order By: Relevance
“…One of the most significant features in many of the tomographic images in central Alaska and along the Aleutians is a high‐velocity zone striking NE‐SW in the upper mantle (Figure ). While some earlier studies (e.g., Qi et al, ) limited this high‐velocity zone to the upper mantle, the most recent work (Burdick et al, ; Martin‐Short et al, ) found it extending to the upper mantle transition zone (MTZ) (Figure ), which is similar to findings from some of the global‐scale tomography studies (e.g., Li et al, ). Whether it also exists in the lower MTZ is unclear, due to limited vertical resolution of the tomographic inversion techniques (Martin‐Short et al, ).…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…One of the most significant features in many of the tomographic images in central Alaska and along the Aleutians is a high‐velocity zone striking NE‐SW in the upper mantle (Figure ). While some earlier studies (e.g., Qi et al, ) limited this high‐velocity zone to the upper mantle, the most recent work (Burdick et al, ; Martin‐Short et al, ) found it extending to the upper mantle transition zone (MTZ) (Figure ), which is similar to findings from some of the global‐scale tomography studies (e.g., Li et al, ). Whether it also exists in the lower MTZ is unclear, due to limited vertical resolution of the tomographic inversion techniques (Martin‐Short et al, ).…”
Section: Introductionsupporting
confidence: 71%
“…Additionally, some continental‐scale tomography studies (e.g., Schaeffer & Lebedev, ) show low velocities down to about 400 km beneath western Canada. The considerable uncertainty about the depth extent of this LVZ is also reflected in the recent tomographic studies shown in Figure (Burdick et al, ; Martin‐Short et al, ).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Recent tomographic images using data from USArray (e.g., Burdick et al, 2017;Porritt et al, 2014;Schmandt et al, 2012) have been used to test the hypothesis that the Yellowstone hot spot has a deep mantle plume origin. Recent tomographic images using data from USArray (e.g., Burdick et al, 2017;Porritt et al, 2014;Schmandt et al, 2012) have been used to test the hypothesis that the Yellowstone hot spot has a deep mantle plume origin.…”
Section: Discussionmentioning
confidence: 99%